Difference between revisions of "Talk:99 questions/Solutions/23"

From HaskellWiki
Jump to: navigation, search
m (some notes)
m (some notes)
 
Line 5: Line 5:
 
the signature of removeAt is:
 
the signature of removeAt is:
 
removeAt :: Int -> [a] -> (a, [a])
 
removeAt :: Int -> [a] -> (a, [a])
so we have to swap the orders of parameters in the calls of remove at from:
+
so we have to swap the orders of parameters in the calls of removeAt from:
 
removeAt l (k+1)
 
removeAt l (k+1)
 
to:
 
to:

Latest revision as of 04:13, 27 July 2017

The more elegant solution using randomRs does not save the new random state and is thus dangerous to use if randomness is important.

some notes

the signature of removeAt is:

   removeAt :: Int -> [a] -> (a, [a])

so we have to swap the orders of parameters in the calls of removeAt from:

   removeAt l (k+1)

to:

   removeAt (k+1) l

and we have to extract the remaining list from the result as well:

   snd $ removeAt (k+1) l

so the full version should be:

   rnd_select2 :: RandomGen g => [a] -> Int -> g -> ([a], g)
   rnd_select2 _ 0 gen = ([], gen)
   rnd_select2 [] _ gen = ([], gen)
   rnd_select2 l count gen
      | count == (length l) = (l, gen)
      | otherwise           =  rnd_select2 (snd $ removeAt (k+1) l) count gen'
                           where (k, gen') =
                                   randomR (0, (length l) - 1) gen
   rnd_selectIO :: [a] -> Int -> IO [a]
   rnd_selectIO l count = getStdRandom $ rnd_select2 l count